The maternal inheritance of the Ashaninka native group from Peru. Issue 1 (December 2019) - Simão, F.; Xavier, C.; Tineo, D.H.; Carvalho, E.F.; Parson, W.; Gusmão, L.
Abstract: The Amazonia rainforest, in South America, harbours native populations with high ethnic diversity. The evaluation of the genetic composition of these populations represents a challenge, and only few studies are available describing its native groups. In this work, the maternal inheritance of 170 Ashaninka individuals living in the Amazonia region of Pasco department, Peru, was evaluated by mtDNA control region sequencing. As previously observed for other native groups from Amazonia, low haplotype diversity was obtained, and only Native American haplogroups were found. Strong founder effects were observed, especially for sub haplogroups A2aa, B2b+152, C1b and D1. During the European colonial period, the Ashaninka population seems to have remained relatively isolated, which can be explained by its remote location in the tropical forest. A comparison with other native South American populations from different linguistic families showed a lack of geographic or linguistic affiliations, highlighting the importance of having specific mtDNA database for the native groups in South America.